Polyethylene over magnetite-multiwalled carbon nanotubes for kerosene removal from water. (January 2022) - Abdullah, Thamer Adnan; Juzsakova, Tatjana; Mansoor, Hadeel; Salman, Ali Dawood; Rasheed, Rashed Taleb; Hafad, Sana Abdulhadi; Mallah, Muhammad Ali; Domokos, Endre; Cuong, Nguyen Xuan; Nadda, Ashok Kumar; Chang, S. Woong; Le, Phuoc-Cuong; et al.
Abstract: In this study, a nano-adsorbent was prepared for kerosene removal from water. Multiwalled carbon nanotubes (MWCNTs) were functionalized with concentrated HNO3 (nitric acid). Subsequently, Fe3 O4 (magnetite) nanoparticles were deposited on the MWCNTs to prepare a magnetite/MWCNTs (Fe-MWCNTs) nanocomposite. Then, polyethylene was added to the Fe-MWCNTs to fabricate a polyethylene/magnetite/MWCNTs (PE/Fe-MWCNTs) novel nanocomposite. The nano-adsorbent was characterized using BET, FTIR, Raman, XRD, TEM, and SEM. A kerosene–water model mixture was used for adsorption tests. Several parameters: adsorption time, adsorbent dose, solution pH, solution temperature, and kerosene concentration in the kerosene-water model mixture, were analyzed during adsorption experiments. After each batch experiment, kerosene concentration was determined using high-performance liquid chromatography (HPLC). Magnetic field was used to remove the adsorbent after each experiment. The kerosene adsorption capacity and removal efficiency of the PE/Fe-MWCNTs nanocomposite (3560 mg/g and 71.2 %, respectively) were higher than those of Fe-MWCNTs, ox-MWCNTs, and fresh MWCNTs (3154 mg/g and 63.1 %, 2204 mg/g and 44.0 %, and 2092 mg/g and 41.8 %, respectively). Kerosene adsorption followed a pseudo-second-order kinetic model (R 2 = 0.999) and the Langmuir isotherm model, suggesting that adsorption was uniform and homogenous process. Highlights: Magnetite nanoparticles were deposited on multiwalled carbon nanotubes. The adsorbent samples were characterized using several analytical methods. The Fe–MWCNT–poly nanocomposite presented high kerosene removal efficiency (71.2 %). Kinetic and isotherm studies were performed. Adsorption mechanisms for the prepared nanocomposites were proposed and discussed.